2020
DOI: 10.1177/0020764020970996
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality, religiosity and the mental health consequences of social isolation during Covid-19 pandemic

Abstract: Background: Evidence shows that religiosity and spirituality (R/S) are highly used in critical moments of life and that these beliefs are associated with clinical outcomes. However, further studies are needed to assess these beliefs during the COVID-19 pandemic. Aims: To evaluate the use of R/S during the COVID-19 pandemic in Brazil and to investigate the association between R/S and the mental health consequences of social isolation. Methods: Cross-sectional study conducted in May 2020. Online surveys were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
108
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 33 publications
11
108
2
9
Order By: Relevance
“…In the context of current pandemic, higher levels of positive religious coping, intrinsic religiosity, and trust in God significantly associated with lower levels of stress and more positive impact of COVID-19, whereas higher levels of negative religious coping and mistrust in God were related to greater stress and negative impacts (Pirutinsky et al 2020 ). Furthermore, higher use of religious and spiritual beliefs during the COVID-19 pandemic was related to better mental health outcomes including hope and spiritual growth (Lucchetti et al 2020 ). There is also a close link between religious coping strategies and loneliness, for example, in a recent study, positive religious coping was found to be negatively associated with loneliness both concurrently and longitudinally (French et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of current pandemic, higher levels of positive religious coping, intrinsic religiosity, and trust in God significantly associated with lower levels of stress and more positive impact of COVID-19, whereas higher levels of negative religious coping and mistrust in God were related to greater stress and negative impacts (Pirutinsky et al 2020 ). Furthermore, higher use of religious and spiritual beliefs during the COVID-19 pandemic was related to better mental health outcomes including hope and spiritual growth (Lucchetti et al 2020 ). There is also a close link between religious coping strategies and loneliness, for example, in a recent study, positive religious coping was found to be negatively associated with loneliness both concurrently and longitudinally (French et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the same review, spirituality was found to aid HCWs in coping with stress, encourage recovery, resilience and reduction in burnout. Another study in Brazil also revealed the significant role of religiosity and spirituality in reducing fear, sorrow and anxiety in relation to the COVID-19 pandemic and consequent social isolation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, research has shown that throughout the pandemic, Google searches for “prayer” (relative to all Google searches), were at the highest level ever recorded, and more than half of the world's population had prayed to end coronavirus (Bentzen, 2020 ). Another study carried out during the pandemic found that religiosity had a positive influence on health outcomes and could minimize the effects of social isolation (Lucchetti et al, 2020 ). However, other studies have shown that highly religious participants reported more unreasonable behavior (e.g., avoiding 5G networks, hoarding toilet paper) than participants with low religiosity, although these behaviors were mediated through emotionality (Kranz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%